2020
DOI: 10.3390/molecules25061395
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrosides and Steroids from the Edible Mushroom Meripilus giganteus with Antioxidant Potential

Abstract: The detailed chemical analysis of the methanol extract of Meripilus giganteus (Pers.) P. Karst. led to the isolation of two new cerebrosides, mericeramides A (1) and B (2) together with cerebroside B (3), ergosterol (4), 3β-hydroxyergosta-7,22-diene (5), cerevisterol (6), 3β-hydroxyergosta-6,8(14),22-triene (7), 3β-O-glucopyranosyl-5,8-epidioxyergosta-6,22-diene (8) and (11E,13E)-9,10-dihydroxy-11,13-octadecadienoic acid (9). The structures of the compounds were determined on the basis of NMR and MS spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Polyporusterone E, detected in the fruiting body of Polyporus umbellatus , is reported to exhibit cytotoxic activity on leukemia 1210 cell proliferation [ 38 ]. Cerebroside B, detected in Meripilus giganteus , has possible antioxidant properties (oxygen radical absorbance capacity [ORAC] 1.69 ± 0.20 mmol TE/g) [ 39 ] and has demonstrated inhibitory effects on the proliferation of human breast cancer in MCF-7 cells [ 40 ]. Cerebroside B concentrations have been described for several edible mushroom species including king oyster (0.95 mg/g dry weight), pearl oyster (1.06 mg/g dry weight), and white button (0.59 mg/g dry weight) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyporusterone E, detected in the fruiting body of Polyporus umbellatus , is reported to exhibit cytotoxic activity on leukemia 1210 cell proliferation [ 38 ]. Cerebroside B, detected in Meripilus giganteus , has possible antioxidant properties (oxygen radical absorbance capacity [ORAC] 1.69 ± 0.20 mmol TE/g) [ 39 ] and has demonstrated inhibitory effects on the proliferation of human breast cancer in MCF-7 cells [ 40 ]. Cerebroside B concentrations have been described for several edible mushroom species including king oyster (0.95 mg/g dry weight), pearl oyster (1.06 mg/g dry weight), and white button (0.59 mg/g dry weight) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of this discussion focuses on interesting (i.e., potential mushroom-specific, bioactive, etc.) compounds detected in our mushroom samples and potential health benefits [ 33 , 37 , 38 , 39 , 40 , 42 ]. As previously mentioned, evidence to support these potential health impacts is based on isolated compounds from mushrooms and not on the consumption of whole, dietary mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, its pharmacological potential seems to be noteworthy. Indeed, different authors demonstrated its antioxidant and antibacterial properties (Karaman et al, 2014;Petrovi c et al, 2022;Sárközy et al, 2020). Alongside these demonstrated abilities, there are some results also in support of the cancer chemopreventive potential of M. giganteus.…”
mentioning
confidence: 86%
“…The oxygen radical antioxidant capacity (ORAC) assay of components of the edible mushroom Meripilus giganteus revealed the highest antioxidant activity (4.94 mmol TE/g) for stellasterol ( 8 ) [ 91 ].…”
Section: Sterolsmentioning
confidence: 99%